Penerapan Identifikasi Bahaya dan Manajemen Resiko Keselamatan di Bandar Udara Supadio - Pontianak - Nurrasjid, M. N. (Warta Penelitian Perhubungan, 2011)
Safety and Security in Airports flight something that should not be ignored. To anticipate a situation that allows the occurrence of accident and incident, the airport operator and all units of the organization that is the environment of the airport should be able to identify hazards I problems based on events that never happened. The survey was conducted in Supadio Airport towards the application of hazard identification and safety risk management, using the method of comparative analysis and evaluation to make mengukuran of 13 variables. Based on measurements of 13 variables, obtained by 3 variables included in the criteria can not be accepted on condition that there is, namely a foreign object variable that has the potential to cause damage to the aircraft (foreign object damage 4.B), the variable things that can disrupt flights (obstacle 4.B), and variable in Apron vehicles (vehicle in Apron 5.C). Two criterion variables risk control/ mitigation requires a management decision that is, variable Noise (noise 5), and variable Security Issues (security issues. 2A). This value indicates that the 3 variables are included that are essential for risk reduction targets.Keywords: Airports, Safety Management System, hazard identification, safety risk